The Role of Green Investment in Achieving Sustainable Marketing - Dimova, Nadezhda (Economy and Business Yearbook, 2022)
In today’s complex and dynamic times, the ever-improving digitalization and automation, the changes in consumer behavior, the tremors in economic and social aspects, are testing the marketing strategies of companies. A number of issues come to the fore, which are related to the challenge of realizing green investments and, at the same time, building successful sustainable marketing strategies. For this reason, studying the role of green investment in achieving sustainable marketing is crucial for the future survival and development of companies and remodeling consumer behavior.